Strategic Planning of IS/IT at RS. Damian Lewoleba with ward and peppard approach - Salamun Rozak; Erwin Sutomo; Yoppy Mirza Maulana (Jurnal Sistem Informasi Universitas Dinamika, 2018)
Damian Lawoleba is private hospital located in Lawoleba East Nusa Tenggara province. One of the most of their effort to achieve competitive advantage is make health service quality improvement with strategy of IS/IT. But in the other hand Damian Lawoleba Hospital is not inpmlementing their IS/IT strategy yet for some of their services. To avoid cost of development of the IS/IT strategy, its need to develop Strategic Planning of Information Systems and Tecnology. Ward and Peppard method is used in the development of Strategic Planning of Information Systems in Damian Lawoleba Hospital. In Preparation Stage, is by doing internal and external analysis for developing business strategy. From this business strategy it will get diversification and horizontal integration strategy.the business strategy will be output of document such as Business IS Strategy, IT Strategy, Management IS/IT Strategy, Future Portofolio Application, and Road map Application that will be used by Damian Lawoleba Hospital as basis for developing information systems and technology.